Response of fattening steers to oral or injected vitamin A, with observations on shrink - McCartor, M.M.; Koch, B.A.; Smith, E.F.; Richardson, D.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
Steers used in an antibiotic study and a trace mineral study reported elsewhere in this publication were also used in a study designed to further evaluate the use of supplemental vitamin A during the fattening period. The animals used showed no visual symptoms of vitamin A deficiency any time. However, the diets fed and the management practices followed were similar to those in studies at other stations where supplemental vitamin A was evaluated.
Keywords: Beef; Oral vs. injected Vitamin A; Shrink